Thermodynamic analysis of reversible hydrogenation for heat storage in concentrated solar power plants - Krieger, Christoph; Müller, Karsten; Arlt, Wolfgang (Solar Energy, 2016)
Heat storage in concentrated solar power plants is required to compensate for variable availability of solar radiation. The energy density achievable with thermochemical heat storage is higher than for molten salt which represents the state of the art technology. The efficiency of different reversible hydrogenation reactions as thermochemical heat storage systems have been examined, since they can be operated at appropriate temperatures. Thermal efficiency of reversible hydrogenation based thermal energy storage can reach values up to 65.9% and an overall efficiency of up to 23.1% compared to 25.7% without heat storage. The LOHC dibenzyltoluene and the metal hydride magnesium hydride turn out to be most suitable for this application. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Thermal energy storage; LOHC; Metal hydride; Thermodynamics